Serum N-Terminal Pro-B-Type Natriuretic Peptide as a Biomarker of Critical Pulmonary Stenosis in Neonates - Lin, Zhiwei; Chen, Yanru; Zhou, Lin; Chen, Sun; Xia, Hongping (Frontiers in Pediatrics, 2022)
Abstract Objectives To determine the efficacy of serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels in predicting critical pulmonary stenosis (CPS) in neonates. Methods All neonates with pulmonary stenosis (PS) admitted to the neonatal intensive care unit of Xinhua Hospital from October 2014 to December 2020 were retrospectively reviewed. Infants with serum NT-proBNP levels measured within 48 hours after birth were enrolled and divided into CP Sand non-CPS groups. Serum NT-proBNP levels and cardiac Doppler indices were compared between the two groups. Correlations were determined using the Spearman’s rank correlation coefficient. Receiver operator characteristic curve analysis was used to explore the predictive value of NT-proBNP for identifying neonatal CPS. Results Among 96 infants diagnosed with PS by echocardiography, 46 were enrolled (21 and 25 in the non-CPS and CPS groups, respectively). Serum NT-proBNP levels were significantly higher in the CPS group than in the non-CPS group [3,600 (2,040–8,251) vs.1,280 (953–2,386) pg/ml, P = 0.003]. Spearman’s analysis suggested a positive correlation between Ln(NT-proBNP) levels and the transvalvular pulmonary gradient (r = 0.311, P = 0.038), as well as between Ln(NT-proBNP) levels and pulmonary artery velocity (r = 0.308, P = 0.040). Receiver operating characteristic curve analysis showed that a cutoff serum NT-proBNP level of 2,395pg/ml yielded a 66.7% and 78.9% sensitivity and specificity for identifying CPS, respectively. The area under the curve was 0.784 (95% CI, 0.637–0.931). A positive correlation was found between Ln(NT-proBNP) and length of hospital stay (r = 0.312, P < 0.05). Conclusion Serum NT-proBNP level was positively correlated with PS severity and could be used as a biomarker to identify CPS in neonates.